INCREASING SIDE EFFECTS OF ENVIRONMENTAL POLLUTION ON HUMAN HEALTH: A STUDY: पर्यावरण प्रदूषण का मानव स्वास्थ्य पर बढ़ता दुष्प्रभाव: एक अध्ययन - Atre, Veena (International Journal of Research -GRANTHAALAYAH, 2015)
There is a very close relationship between environment and human health. Today, in the era of industrialization, the environment is contaminated, so how can we imagine clean food, water and air? As a result, many diseases are born in humans. The main elements of environment are land, water, air, flora and fauna. Water and Health: Tomorrow, the contaminated water of factories mixes in the river drains and pollutes excessive water. Drinking polluted water gives rise to diseases like dermatitis, polio, jaundice, typhoid, fever, dysentery, diarrhea, worm leptosporis, conjunctiva, dentistry, fluorosis, miscarriage, slow growth. Consumption of excessive amount of chloride in drinking water causes black spots in the teeth of the person. Bathing in polluted water in India is increasing the number of skin patients. Air pollution: Air pollution is caused by the presence of unwanted gases in the air. Yesterday there is difficulty in breathing due to the smoke emanating from factories and motor vehicles. If the amount of hydrocarbons in the air increases then the decrease in vision power, the amount of sulfuride oxide increases, then diseases like asthma, central nervous system are affected due to lack of oxygen in the blood from carbonamonoxide pollutants. Thus air pollution gives rise to incurable diseases. Cough, dermatitis, genital mutations, gene changes, genetic risks have increased. पर्यावरण और मानव स्वास्थ्य का अत्यंत घनिष्ठ सम्बन्ध है। आज औद्योगीकरण के दौर में पर्यावरण ही दूषित है तो स्वच्छ भोजन पानी एवं वायु की कल्पना कैसे ही जा सकती है। इसके फलस्वरूप मनुष्य में अनेक रोगों का जन्म होता है। पर्यावरण के मुख्य तत्व भूमि, जल,वायु, वनस्पति एवं प्राणी समूह है। जल एवं स्वास्थ्य: कल कारखानों का दूषित जल नदी नालों में मिलकर अत्यधिक जल प्रदूषित करता है। प्रदूषित जल पीने से त्वचा रोग, पोलियो, पीलिया, टाईफाईड, बुखार, पेचिस, अतिसार, कृमि लेप्टोस्पाईस, कंेसर, दंतक्षय, फ्लूओरोसिस, गर्भपात, मंद विकास जैसी बीमारियों को जन्म देते हैं। पेयजल में क्लोराइड की अधिक मात्रा के सेवन से व्यक्ति के दाँतों में काले धब्बे पड़ जाते है’ रीढ़ की हड्डी तथा जोड़ों की हड्डी जकड़ जाती है। भारत में प्रदूषित जल में स्नान करने से त्वचा रोगियों की संख्या बढ़ रही है। वायु प्रदूषण:हवा में अवांछित गैसों की उपस्थिति से वायु प्रदूषण होता है। कल कारखानों और मोटर वाहनों से निकलने वाले धुएँ के कारण साँस लेने में कठिनाई होती है। वायु में यदि हाइड्रोकार्बन की मात्रा बढ़ती है तो दृष्ट शक्ति में कमी, सल्फरडाई आक्साइड की मात्रा बढ़ती है तो दमा जैसे रोग, कार्बनमोनो आक्साइड प्रदूषक से रक्त में आॅक्सीजन की कमी के कारण केन्द्रीय स्नायुतंत्र प्रभावित होता है। इस प्रकार वायु प्रदूषण असाध्य रोगों को जन्म देते है। खाँसी, त्वचारोग, जननिक विकृति का उत्पन्न होना जीन परिवर्तन, आनुवांषिकीय खतरे बढ़े है।